The Influence of Product Quality, Service Quality, and Location on Customer Loyalty at Depot Wakik Gresik - Rahmah Renanda Fantika; J.E. Sutanto; Moses Soediro; Adrie Oktavio (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research entitled "The influence of product quality, service quality, and location on customer loyalty at Depot Wakik Gresik" has four objectives, namely: (1) To find out what effect product quality has on customer loyalty, (2) To find out how service quality influences on customer loyalty, (3) Knowing how location influences customer loyalty, (4) Knowing how product quality, service quality, and location influence customer loyalty simultaneously. The Depot Wakik Gresik is a business engaged in the food and beverage sector which is located in Gresik Regency. With the quantitative method also using the research population which are customers of the Depot Wakik Gresik who have visited by buying and consuming at Depot Wakik Gresik products more than twice, researchers candone. The sample used was 150 respondents. The required data was collected using questionnaires to the respondents directly. Data is processed using IBM SPSS 25 software for windows. The results obtained in this research are product quality, service quality, and location have a positive and significant effect both partially and simultaneously on customer loyalty at the Depot Wakik Gresik.